2016
DOI: 10.14260/jemds/2016/1222
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Pharyngeal Orifice of Auditory Tube

Abstract: Eustachian tube extends from the anterior wall of the middle ear to the lateral wall of the nasopharynx at the level of inferior nasal choncha. It maintains the equilibrium of air. It is an important landmark for endoscopic evaluation in patients with chronic otitis and also for the transnasal approach to the infratemporal fossa. MATERIALS AND METHODSStudy was carried out, 50 sagittal sections (25 right side and 25 left side) of head and neck specimens from adult formalin fixed cadavers from the Department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…Mohite et al observed that the most common shape of the pharyngeal opening was oval, while the present study reported slit-like as the most common shape [ 9 ].…”
Section: Discussioncontrasting
confidence: 48%
“…Mohite et al observed that the most common shape of the pharyngeal opening was oval, while the present study reported slit-like as the most common shape [ 9 ].…”
Section: Discussioncontrasting
confidence: 48%
“…Triangular shape was more common on both right and left side. Very few authors like Bluestone [2] have worked on pharyngeal opening but have taken only vertical length [3]. According to the study done by Mohite et al, the vertical height was recorded to be 0.92cm on right side and 0.81cm on left side.…”
Section: Discussionmentioning
confidence: 99%
“…*2 Assistant Professor, Department of Anatomy, K S Hegde Medical Academy, Mangaluru, Karnataka, India. 3 Lecturer, Department of Anatomy, K S Hegde Medical Academy, Mangaluru, Karnataka, India. 4 Professor, Department of Anatomy, K S Hegde Medical Academy, Mangaluru, Karnataka, India.…”
mentioning
confidence: 99%